Inflammation and necrosis syndrome in young piglets : a longitudinal study - Becker, Sabrina; Hindenlang, Katrin; Kuehling, Josef; Lechner, Mirjam; Reiner, Gerald; Justus Liebig University Giessen (My University, 2025)
Swine Inflammation and Necrosis Syndrome (SINS) is a simple and non-invasive animalbased health and welfare indicator that combines the clinical observation of bristle loss, swelling, redness, exudation, necrosis and haemorrhage in various parts of the body. It provides a point-of-care measure with direct intervention capability. Several studies from different countries demonstrate its considerable prevalence, particularly among newborn, suckling and weaned piglets. The syndrome has been demonstrated to be endogenous, as evidenced by clinical, pathohistological, clinical chemical, metabolomic, transcriptomic and genomic analysis. It has been established that the first and fourth weeks of life represent suitable time points for examination. However, longitudinal follow-up of individual animals has hitherto been lacking. In order to address this issue, a total of 1080 complete SINS examinations were conducted on 59 piglets at days 1 to 14, 19, 22, 26 and 41 of life. The findings substantiate the bimodal progression and evince a robust correlation between signs in disparate anatomical regions, including body temperature. Two Peaks with significantly increased SINS signs were observed, the first around the fourth day of life and the second around day 26. The majority of indications of SINS in the second Peak manifested prior to the initiation of the weaning process. The development of SINS signs in the piglets as a group followed a clear pattern. However, it was not feasible to predict the subsequent course of SINS based on individual animals. It is recommended that SINS, as an animal-based health and welfare indicator, be screened on days three to four and/or in the fourth week of life. It is imperative that the day of life is specified with the greatest possible precision, given the propensity for considerable deviations to occur within a timeframe of one to three days, especially during the initial week of life. The implementation of these findings has the potential to make a decisive contribution to improving inventory herd analyses and studies on SINS, thereby improving the welfare and health of piglets.
Keywords: ddc:630